Financial Impacts of Late-Gestation Heat Stress on Cow and Offspring Lifetime Performance: AN374/AN374, 11/2021 - Casarotto, L. T.; Laporta, J.; Dahl, G. E. (EDIS, 2021)
This publication describes the financial implications of ignoring heat stress in dry cows to assist dairy producers in decisions about installation of heat abatement measures and cooling cows in that stage of the production cycle. Written by L. T. Casarotto, J. Laporta, and G. E. Dahl, and published by the UF/IFAS Department of Animal Sciences, November 2021.